BIOLOGICAL TREATMENT PLANTS SMALL QUANTITIES OF SEWAGE «BIOTAL» - , А. И. (Municipal economy of cities. Series: «Economy science», 2013)
Disclosed is a question of the biological features of the treatment of domestic wastewater of small volumes. The basic requirements to be met by a small treatment plant. The description of technology «BIOTAL» for biological treatment of small volumes of wastewater.